Esophageal Carcinoma Histology Affects Perioperative Morbidity Following Open Esophagogastrectomy. (5th February 2009) - Woodall, Charles E.; Duvall, Ryan; Scoggins, Charles R.; McMasters, Kelly M.; Martin, Robert C. G.
Abstract : Background . Esophagectomy for esophageal cancer is being practiced routinely with favorable results at many centers. We sought to determine if tumor histology is a powerful surrogate marker for perioperative morbidity. Methods . Seventy three consecutive patients managed operatively were reviewed from our prospectively maintained database. Results . Adenocarcinoma (AC) was present in 52 (71%) and squamous cell (SCC) in 21 (29%). The use of neoadjuvant therapy was similar for the AC (34.62%) and SCC (42.86%) groups. The SCC group had a higher incidence of prior pulmonary disease than the AC group (23.8% versus 5.8%, resp.;P = .03). SCC patients were more likely to have a prolonged ICU stay than AC patients (P = .004 ) despite similar complication rates, EBL, and prognostic nutritional index. The SCC group did, however, experience higher grades of complications (P = .0053 ). Conclusions . Presence of SCC was the single best predictor of prolonged ICU stay and more severe complications as defined by this study. Only a past history of pulmonary disease was different between the two histologic subgroups.